Ameloblast transcriptome changes from secretory to maturation stages. (August 2014) - Simmer, James P.; Richardson, Amelia S.; Wang, Shih-Kai; Reid, Bryan M.; Bai, Yongsheng; Hu, Yuanyuan; Hu, Jan C.-C.
Abstract The purpose of this study was to identify the major molecular components in the secretory and maturation stages of amelogenesis through transcriptome analyses. Ameloblasts (40 sections per age group) were laser micro-dissected from Day 5 (secretory stage) and Days 11–12 (maturation stage) first molars. PolyA+ RNA was isolated from the lysed cells, converted to cDNA, and amplified to generate a cDNA library. DNA sequences were obtained using next generation sequencing and analyzed to identify genes whose expression had increased or decreased at least 1.5-fold in maturation stage relative to secretory stage ameloblasts. Among the 9198 genes that surpassed the quality threshold, 373 showed higher expression in secretory stage, while 614 genes increased in maturation stage ameloblasts. The results were cross-checked against a previously published transcriptome generated from tissues overlying secretory and maturation stage mouse incisor enamel and 34 increasing and 26 decreasing expressers common to the two studies were identified. Expression of F2r, which encodes protease activated receptor 1 (PAR1) that showed 10-fold higher expression during the secretory stage in our transcriptome analysis, was characterized in mouse incisors by immunohistochemistry. PAR1 was detected in secretory, but not maturation stage ameloblasts. We conclude that transcriptome analyses are a good starting point for identifying genes/proteins that are critical for proper dental enamel formation and that PAR1 is specifically expressed by secretory stage ameloblasts.